2022
DOI: 10.1155/2022/8594022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Organ Metastases on the Prognosis of Stage IV Urothelial Carcinoma of the Bladder

Abstract: Objective. To assess the prognosis of stage IV metastatic urinary bladder urothelial carcinoma (UBUC) at initial diagnosis and determine prognostic factors based on distant organ metastasis. Methods. A retrospective cohort analysis of UBUC was conducted based on the Surveillance, Epidemiology, and End Results (SEER) database. Univariate and multivariate Cox regression analyses were used to determine the variables associated with overall survival (OS). Kaplan–Meier curves were used to compare survival curves am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Liu et al . [34 ▪ ] have confirmed that surgery of the primary site (endoscopic resection or cystectomy) is an independent protective factor and that the number of metastatic sites predicts OS, irrespectively of the type of the organs involved. Of course, the SEER data are partly lacking important clinical variables that should be controlled for (e.g.…”
Section: Role Of Primary Tumour and Metastases Treatment In Synchrono...mentioning
confidence: 55%
“…Liu et al . [34 ▪ ] have confirmed that surgery of the primary site (endoscopic resection or cystectomy) is an independent protective factor and that the number of metastatic sites predicts OS, irrespectively of the type of the organs involved. Of course, the SEER data are partly lacking important clinical variables that should be controlled for (e.g.…”
Section: Role Of Primary Tumour and Metastases Treatment In Synchrono...mentioning
confidence: 55%
“…Simultaneous metastases to other sites were common in UTUC patients with BM and significantly reduced their survival rates [ 7 , 29 ]. Liu et al suggested that the prognosis of stage IV metastatic uroepithelial carcinoma depends on the number of metastases from other organs, with no difference in OS compared to other metastatic sites when using bone metastasis as a reference [ 30 ]. Importantly, our findings contrast with those of Zhou et al [ 7 ], who reported that lung metastasis was identified as a risk factor for OS in UTUC patients with BM.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of patient backgrounds showed that patients with mUTUC had higher frequency of lung metastasis than those with mUBC. Liu et al reported that the sites of metastasis in 1,035 patients with stage IV metastatic bladder cancer were lymph nodes in 25.4%, bone in 24.7%, lung in 19.4%, liver in 18.1%, and brain in 3.1% (26). Chen et al reported that the sites of metastasis in 424 patients with metastatic renal pelvic carcinoma were lymph nodes in 30.0%, bone in 36.1%, lung in 45.3%, liver in 32.3%, and brain in 2.8%, respectively (27).…”
Section: Discussionmentioning
confidence: 99%